THE IMPACT OF HIGH TEMPERATURES ON COGNITIVE, PHYSIOLOGICAL, AND THERMAL PERCEPTION IN TROPICAL AREAS - Fauziah, Ayu
Global climate change has led to increased environmental temperatures in various parts of the world, raising concerns about human health and productivity, particularly in terms of exposure to extreme heat. This is a growing concern as technological developments have shifted work from physical activity to tasks that require cognitive abilities. The impact of heat exposure is becoming an increasingly real challenge in the world of work. Although the impact of high temperatures on the body has been widely reported, the results still vary and are more common in non-tropical countries. The purpose of this research is to examine the influence of heat and types of cognitive tasks on the physiological, cognitive, and thermal perception functions of people in tropical areas. The research method used is an experimental method with a within-subject design. The independent variable in this study is temperature, which consists of 3 levels: 24°C, 30°C, and 39°C, and types of cognitive tasks consisting of a counting task and a change blindness task. During the experiment, participants were asked to perform cognitive tasks to assess cognitive performance, while heart rate and brain waves were continuously monitored, and assessments of thermal sensation and comfort were recorded. A total of 9 men and 9 women participated in three phases of the experiment. Based on experimental data, it shows that higher temperatures cause a decrease in cognitive performance in both the change blindness task and counting task, as well as an increase in heart rate. At a temperature of 39°C, attention is the cognitive function most easily affected by high temperatures. The higher the heat exposure temperature, the higher the mental load required to complete the task, as well as increased discomfort and a stronger sensation of heat. There was a lower delta brain wave activity and higher beta and theta wave activity with an increase in heat exposure temperature. Furthermore, based on tests on gender, women are found to be more resistant to heat stress than men.